SEASONAL CHANGES OF LOW MOLECULAR WEIGHT DICARBOXYLIC ACIDS IN SNOW SAMPLES FROM DOME FUJI STATION, ANTARCTICA - マツナガ, ソウ; カワムラ, キミタカ; ヤマモト, ヨシキ; アズマ, ノブヒコ; フジイ, ヨシユキ; モトヤマ, ヒデアキ; MATSUNAGA, Sou; KAWAMURA, Kimitaka; YAMAMOTO, Yoshiki; AZUMA, Nobuhiko; FUJII, Yoshiyuki; MOTOYAMA, Hideaki (National Institute of Polar Research, 1999)
P(論文) Fresh snow samples were collected at Dome Fuji Station, Antarctica, from October 1995 to November 1996,and were analyzed for dicarboxylic acids by capillary gas chromatography and mass spectrometry. Concentrations of oxalic acid (C_2,the most abundant diacid) ranged from 2.07 to 17.4μg/kg-snow. C_2-C_8 dicarboxylic acids showed clear seasonal changes with higher concentration in summer than in winter. This suggested that low molecular weight dicarboxylic acids were produced by photochemical reactions. Concentrations of dicarboxylic acids at Dome Fuji Station were about 20 times higher than the snow samples collected on the route from Syowa Station to Dome Fuji Station. The concentrations of maleic acid and phthalic acid (derived from photochemical oxidation of anthropogenic aromatic hydrocarbons) at Dome Fuji Station was about 40 times higher than the route samples. In contrast, the concentrations of C_8 and C_9 diacids (derived from photochemical oxidation of biogenic unsaturated fatty acids) at Dome Fuji Station were only 3-5 times higher than the route samples. This comparison suggests that surface snow samples at Dome Fuji Station contained photooxidation products of anthropogenic organic matter, suggesting that the diacids are emitted from incomplete combustion of fossil fuel used at the Station and/or produced in the atmosphere by photooxidation of exhaust gases. On the other hand, concentration ratios of fumaric acid (trans-C_4 unsaturated diacid) to maleic acid (cis-C_4 unsaturated diacid) showed higher values in summer than in winter, suggesting that cis to trans isomerization occurs photochemically in the atmosphere and possibly in the snow surface. Although the atmosphere over Dome Fuji Station is contaminated by diesel exhaust from the station, seasonal distribution of dicarboxylic acids in fresh snow samples provide useful information on photochemical reactions occurring in the polar atmosphere. departmental bulletin paper